The Influence of Parental Pressure on Children's Future Career Development - Ratna Wulandari; Soraya; Muhammad Imbang; Shofiya (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
Abstrak: Authoritarian pressure from parents in determining their children's educational and career directions often has a negative impact on the psychological health and learning motivation of adolescents. This study aims to analyze in-depth the impact of such pressure on adolescent career development, as well as to evaluate the effectiveness of Client-Centered counseling intervention in helping individuals achieve optimal self-adjustment. This research uses a qualitative method with a clinical/psychological single-case study design. The research subject was a 17-year-old female student, who was identified as experiencing future anxiety (overthinking), declining academic performance, and forming a dual-personality mechanism due to parental coercion to enter the science major (Natural Sciences/IPA). Data collection was conducted using triangulation through in-depth interviews, observations. The results showed that the Client-Centered intervention, based on unconditional positive regard, proved effective in facilitating the subject to independently realize her internal conflicts, reduce anxiety, and restore her autonomy to plan assertive communication with her family. This study concludes that the recovery of a fragmented adolescent self-concept due to family repression is a primary prerequisite in career conflict resolution, which simultaneously emphasizes the importance of emotional freedom space in determining a child's future. Keywords: Parental Pressure, Career Development, Client-Centered Counseling, Case Study, Adolescent Autonomy.